2015
DOI: 10.1016/j.ijscr.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

From radial head to radiocapitellar to total elbow replacement: A case report

Abstract: HighlightsOverstuffing is a serious yet avoidable complication of radial head arthroplasty.Overstuffing severely alters elbow joint kinematics and leads to capitellar erosion.Radiocapitellar arthroplasty can be a salvage procedure in such cases.Limited clinical data is available thus far regarding radiocapitellar arthroplasty.The possibility for early failure due to ulnohumeral erosion has to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Burkhart et al (2015) have done follow-up examinations of 21 patients who were treated with angular stable plates (APTUS ® 2,0 mm proximal radius plates, Medartis ® , Basel, Switzerland). The patients' follow-up examination was done after 12,1 months [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] on average and a lack of extension of 12,1°(0-30°), an average flexion of 136,7°( 100-150°), as well as a pronation and a supination of 70,9°(40-80°), respectively 63,3°(20-80°) was documented. 20 In our study we observed a lack of extension of 12,7°(10°; 0-30°) and a flexion of 119°(122°; 90-140°), as well as a pronation and supination of 71°(80°; 10-90°), respectively 59,3°(70°; 5-90°).…”
Section: Discussionmentioning
confidence: 99%
“…Burkhart et al (2015) have done follow-up examinations of 21 patients who were treated with angular stable plates (APTUS ® 2,0 mm proximal radius plates, Medartis ® , Basel, Switzerland). The patients' follow-up examination was done after 12,1 months [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] on average and a lack of extension of 12,1°(0-30°), an average flexion of 136,7°( 100-150°), as well as a pronation and a supination of 70,9°(40-80°), respectively 63,3°(20-80°) was documented. 20 In our study we observed a lack of extension of 12,7°(10°; 0-30°) and a flexion of 119°(122°; 90-140°), as well as a pronation and supination of 71°(80°; 10-90°), respectively 59,3°(70°; 5-90°).…”
Section: Discussionmentioning
confidence: 99%
“…The most common issues are overstuffing, dissociation of the head component, (sub)luxation, malalignment and loosening. 42 , 49 …”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Welche Rolle der hemilaterale Gelenkersatz bei chronischer knöcherner Instabilität in Zukunft einnehmen kann, ist jedoch bei fehlenden klinischen Ergebnissen noch nicht geklärt. Zu bedenken ist, dass sich Rückzugsmöglichkei-ten bei Lockerung oder persistierender Instabilität auf die Totalendoprothese beschränken [8,15].…”
Section: Radiohumerale Rekonstruktionunclassified